2017
DOI: 10.1038/eye.2017.85
|View full text |Cite
|
Sign up to set email alerts
|

Acute endophthalmitis after cataract surgery: 164 consecutive cases treated at a referral center in South Korea

Abstract: PurposeTo identify prognostic factors in patients referred with endophthalmitis after cataract surgery, and to evaluate the efficacy of primary vitrectomy as an initial management.MethodsOver an eight-year study period, we retrospectively reviewed the medical records of 164 patients who were referred with endophthalmitis following cataract surgery. Treatment generally conformed to standard guidelines, although primary vitrectomy was performed in several eyes with a visual acuity of hand motion or better, depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
(9 reference statements)
1
29
0
1
Order By: Relevance
“…Previous studies have reported that sex was not significantly related to final VA. [ 13 , 14 ] Other studies have demonstrated that sex was significantly associated with final visual outcome. [ 9 , 11 ] Consistent with second group of studies, [ 9 , 11 ] our study showed a significant association between sex and final visual outcome.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have reported that sex was not significantly related to final VA. [ 13 , 14 ] Other studies have demonstrated that sex was significantly associated with final visual outcome. [ 9 , 11 ] Consistent with second group of studies, [ 9 , 11 ] our study showed a significant association between sex and final visual outcome.…”
Section: Discussionsupporting
confidence: 92%
“…[ 7 ] However, several recent studies have reported the efficacy and advantages of early primary vitrectomy for postcataract endophthalmitis, and early primary vitrectomy has become one option for patients with VA better than LP. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Após a facectomia, os pacientes do GC necessitaram de poucas revisões cirúrgicas, que não estavam relacionadas a complicações infecciosas. Em contraste, os pacientes com endoftalmite foram submetidos a pelo menos uma e até três revisões cirúrgicas, como consequência direta da evolução do caso, o que está de acordo com estudos que descrevem o tratamento da endoftalmite 3,6,7,19 . O número de retornos para o acompanhamento pós-operatório de pacientes com endoftalmite (GE) foi significativamente maior do que o GC.…”
Section: Discussionunclassified
“…Other study reported the age of patients at diagnosis ranged between 56-84 years old. 12 Age over 50 years old is a factor associated with poor outcomes in final VA. 13 Cases with presenting visual acuity better than light perception (LP) is a significant factor for achieving better final visual acuity. 10 In this study, it was found that cases with initial VA better than 1/300 could get improvement in final VA by 50%, while cases with initial VA worse than 1/300 only 2 out of 5 cases (40%) had better final vision.…”
Section: Fitria Romadiana Et Al International Journal Of Medical and mentioning
confidence: 99%